EXPERIENCE OF USING THE DRUG GEPON IN THE TREATMENT OF PATIENTS FOCAL SCLERODERMA - Narzikulov R. M. (International Journal of Innovations in Engineering Research and Technology, 2021)
We conducted a study of the effectiveness of the drug gepon in focal (localized) scleroderma. The main study group consisted of 19 patients with focal scleroderma aged 22 to 45 years. Among the patients, 11 men and 8 women. The duration of the disease varied from 3 to 10 years. Skin lesions were limited in nature, more often localized mainly on the face, chest, abdomen and lower leg. In addition to Gepon, patients were treated with traditional methods of treatment. We have obtained the following conclusions: the inclusion of the drug Gepon in the complex treatment of focal (localized) scleroderma contributes to a faster resolution of the pathological process and the restoration of skin elasticity.